Transfusion Practices in Pediatric Cardiac Surgery Requiring Cardiopulmonary Bypass: A Secondary Analysis of a Clinical Database. Issue 11 (November 2021) - Hanson, Sheila J.; Karam, Oliver; Birch, Rebecca; Goel, Ruchika; Patel, Ravi M.; Sola-Visner, Martha; Sachais, Bruce S.; Hauser, Ronald G.; Luban, Naomi L. C.; Gottschall, Jerome; Josephson, Cassandra D.; Hendrickson, Jeanne E.; et al.
Abstract : OBJECTIVES: To describe blood component usage in transfused children with congenital heart disease undergoing cardiopulmonary bypass surgery across perioperative settings and diagnostic categories. DESIGN: Datasets from U.S. hospitals participating in the National Heart, Lung, and Blood Institute Recipient Epidemiology and Donor Evaluation Study-III were analyzed. SETTING: Inpatient admissions from three U.S. hospitals from 2013 to 2016. PATIENTS: Transfused children with congenital heart disease undergoing single ventricular, biventricular surgery, extracorporeal membrane oxygenation. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Eight hundred eighty-two transfused patients were included. Most of the 185 children with single ventricular surgery received multiple blood products: 81% RBCs, 79% platelets, 86% plasma, and 56% cryoprecipitate. In the 678 patients undergoing biventricular surgery, 85% were transfused plasma, 75% platelets, 74% RBCs, and 48% cryoprecipitate. All 19 patients on extracorporeal membrane oxygenation were transfused RBCs, plasma, and cryoprecipitate, and 18 were transfused platelets. Intraoperatively, patients commonly received all three components, while postoperative transfusions were predominantly single blood components. Pretransfusion hemoglobin values were normal/low-normal for age for all phases of care for single ventricular surgery (median hemoglobin 13.2–13.5 g/dL). Pretransfusion hemoglobin values for biventricular surgeries were higher intraoperatively compared with other timing (12.2 g/dL vs 11.2 preoperative and postoperative; p < 0.0001). Plasma transfusions for all patients were associated with a near normal international normalized ratio: single ventricular surgeries median international normalized ratio was 1.3 postoperative versus 1.8 intraoperative and biventricular surgeries median international normalized ratio was 1.1 intraoperative versus 1.7 postoperative. Intraoperative platelet transfusions with biventricular surgeries had higher median platelet count compared with postoperative pretransfusion platelet count (244 × 10 9 /L intraoperative vs 69 × 10 9 /L postoperative). CONCLUSIONS: Children with congenital heart disease undergoing cardiopulmonary bypass surgery are transfused many blood components both intraoperatively and postoperatively. Multiple blood components are transfused intraoperatively at seemingly normal/low-normal pretransfusion values. Pediatric evidence guiding blood component transfusion in this population at high risk of bleeding and with limited physiologic reserve is needed to advance safe and effective blood conservation practices. Abstract : Supplemental Digital Content is available in the text.